Solar Collectors and Panels Theory and Applications - Manyala, Reccab (IntechOpen, 2010)
This book provides a quick read for experts, researchers as well as novices in the field of solar collectors and panels research, technology, applications, theory and trends in research. It covers the use of solar panels applications in detail, ranging from lighting to use in solar vehicles.